Epigenome profiling reveals significant DNA demethylation of interferon signature genes in lupus neutrophils. (April 2015) - Coit, Patrick; Yalavarthi, Srilakshmi; Ognenovski, Mikhail; Zhao, Wenpu; Hasni, Sarfaraz; Wren, Jonathan D.; Kaplan, Mariana J.; Sawalha, Amr H.
Abstract: Recent evidence suggests that neutrophils play an important role in the pathogenesis of lupus. The goal of this study was to characterize the epigenetic architecture, by studying the DNA methylome, of neutrophils and low density granulocytes (LDGs) in lupus patients. We studied 15 lupus patients and 15 healthy age, sex, and ethnicity matched controls. Genome-wide DNA methylation was assessed using the Illumina HumanMethylation 450 BeadChip array, which includes over 485, 000 methylation sites across the entire genome. Bisulfite DNA sequencing was used to validate the array results. Statistical and bioinformatic analysis was performed to identify and characterize differentially methylated loci and genes. We identified 293 differentially methylated CG sites in neutrophils between lupus patients and controls. The majority (68%) of differentially methylated CG sites were hypomethylated in lupus neutrophils compared to controls, suggesting overall hypomethylation. We found a robust and consistent demethylation of interferon signature genes in lupus neutrophils, and similar demethylation in the same genes in autologous LDGs. Indeed, the DNA methylome in lupus neutrophils and LDGs was almost identical, suggesting similar chromatin architecture in the two granulocyte subsets. A notable exception was the hypomethylation of a CG site in the promoter region of the cytoskeleton-regulating gene RAC1 in LDGs. Our findings demonstrate a pattern of robust demethylation of interferon signature genes in lupus patients supporting a pathogenic role for neutrophils in lupus. We suggest a model whereby DNA from lupus neutrophils and LDGs externalized by NETosis enhance type-I IFN production via TLR-9 stimulation by hypomethylated DNA. Highlights: This is the first epigenetic study in lupus neutrophils and low density granulocytes (LDGs). Interferon-regulated genes are strongly demethylated in lupus neutrophils. The DNA methylome of LDGs is almost identical to mature neutrophils in lupus. The cytoskeleton-related gene RAC1 is hypomethylated in lupus LDGs compared to neutrophils.